Producción de un documental audio-visual dirigido a estudiantes sobre la historia de la universidad técnica de cotopaxi mediante el empleo de herramientas tecnológicas disponibles en el laboratorio de diseño gráfico computarizado, en el período 2013 - Segura Tobar, Juan Carlos (2015)
This documentary is a narrative of the university history and its cognitive significance for social improvement, since the digital perspective for the incorporation of multimedia resource as a tool for broadcasting information perennial, looking for a goal directed to innovation, to produce a documentary audio-visual for students on the history of the Technical University of Cotopaxi, through the use of technological tools available in the laboratory of computerized graphic design, in the period 2013. In where it is focused by a need to strengthen the institutional image that would position the academic excellence that forms in the classrooms of the Institution, radiating toward the community, This documentary is a narrative of the university history and its cognitive significance for social improvement, since the digital perspective for the incorporation of multimedia resource as a tool for broadcasting information perennial, looking for a goal directed to innovation, to produce a documentary audio-visual for students on the history of the Technical University of Cotopaxi, through the use of technological tools available in the laboratory of computerized graphic design, in the period 2013. In where it is focused by a need to strengthen the institutional image that would position the academic excellence that forms in the classrooms of the Institution, radiating toward the community....